KISARAN INANG WERENG PUCUK METE (Sanurus indecora) DI PEMBIBITAN - Rahayu, M; Nurmas, Andi; Yunita, Yunita (Jurnal Agroteknos, 2012)
Cashew  is one of export commodities that has high economic value compared to other commodities.   Sanurus indecora is  one of major pest in cashew, because the pest could decrease both quality and quantity of the products. This study aimed to determine the most preferred host of  S. indecora. The study consisted of: (1) Treatment of food, Choice – method using 10 tail nymphs S. indecora and No-choice method  using 30 individuals of S. indecora (2) The treatment was done by spawning  no-choice method using a single pair of imago S. indecora and Choice-method using 10 pairs of S. indecora. The parameters observed were the number of S. indecora attack on any type of host plant and the number of eggs laid on each  host  plant  species.  The  study  found  that  the  treatment of  feed  no-choice method, nymphs that attacked on mango plants was on average of 8.5 tail, cashew plant 6.5 and rambutan 2.5 tail. Treatment of feed, choice-method,  an average selection of nymphs that attacked the mango plants was 20 tail, cashew plants 5 tail and   rambutan plants 1.5 tail. Spawning, no-choice method, the average number of eggs laid  was 35 on mango plants, cashew plants 16 eggs laid, while no egg laid. Spawning  choice-method the average number of eggs laid was 86 on mango plants, 50.5 on cashew plant while on rambutan plants. The results showed that the most preferred host of S. indecora was mango plant. Keywords: cashew plant, host range, S. Indecora